Beyond Leadership: Why Lecturer Competence Dominates Research Productivity in Higher Education? - Galih Permana; Mahmud Mahmud; Bambang Samsul Arifin; Qiqi Yuliati Zaqiah; Badrudin Badrudin (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
The inequality in lecturers' research productivity indicates that academic performance is not only determined by individual abilities but is also influenced by organizational leadership and lecturer competency. This study aims to analyze the influence of transformational leadership, pedagogical competence, and professional competence on lecturers' research productivity. The study used a quantitative, cross-sectional survey design with a census of 60 lecturers. Data were collected using a Likert-scale questionnaire and analyzed using SPSS 26.0 for correlation and regression. The results showed that transformational leadership had a significant effect on research productivity (β = 0.329; R² = 0.110), while pedagogical competence (β = 0.813; R² = 0.833) and professional competence (β = 0.840; R² = 0.822) had a stronger influence. Simultaneously, the three variables explained 85.1% of the variation in lecturers' research productivity (R² = 0.851). This research implies that increasing lecturers' research productivity requires synergy between transformational leadership and strengthening pedagogical and professional competencies through structured, performance-based, and institutionally sound development programs to foster a culture of sustainable research within higher education.